Embryological Origin of Human Smooth Muscle Cells Influences Their Ability to Support Endothelial Network Formation. (18th May 2016) - Bargehr, Johannes; Low, Lucinda; Cheung, Christine; Bernard, William G.; Iyer, Dharini; Bennett, Martin R.; Gambardella, Laure; Sinha, Sanjay
Abstract : Smooth muscle cells (SMCs) from distinct embryonic origins differ in their ability to support human umbilical vein endothelial cell (HUVEC) network formation. Lateral mesoderm-derived SMCs best supported endothelial cell network complexity and survival in vitro, in part through increased expression of midkine. A lineage-specific approach might be beneficial for vascular tissue engineering and therapeutic revascularization. Abstract: : Vascular smooth muscle cells (SMCs) from distinct anatomic locations derive from different embryonic origins. Here we investigated the respective potential of different embryonic origin-specific SMCs derived from human embryonic stem cells (hESCs) to support endothelial network formation in vitro. SMCs of three distinct embryological origins were derived from an mStrawberry-expressing hESC line and were cocultured with green fluorescent protein-expressing human umbilical vein endothelial cells (HUVECs) to investigate the effects of distinct SMC subtypes on endothelial network formation. Quantitative analysis demonstrated that lateral mesoderm (LM)-derived SMCs best supported HUVEC network complexity and survival in three-dimensional coculture in Matrigel. The effects of the LM-derived SMCs on HUVECs were at least in part paracrine in nature. A TaqMan array was performed to identify the possible mediators responsible for the differential effects of the SMC lineages, and a microarray was used to determine lineage-specific angiogenesis gene signatures. Midkine (MDK) was identified as one important mediator for the enhanced vasculogenic potency of LM-derived SMCs. The functional effects of MDK on endothelial network formation were then determined by small interfering RNA-mediated knockdown in SMCs, which resulted in impaired network complexity and survival of LM-derived SMC cocultures. The present study is the first to show that SMCs from distinct embryonic origins differ in their ability to support HUVEC network formation. LM-derived SMCs best supported endothelial cell network complexity and survival in vitro, in part through increased expression of MDK. A lineage-specific approach might be beneficial for vascular tissue engineering and therapeutic revascularization. Significance: Mural cells are essential for the stabilization and maturation of new endothelial cell networks. However, relatively little is known of the effect of the developmental origins of mural cells on their signaling to endothelial cells and how this affects vessel development. The present study demonstrated that human smooth muscle cells (SMCs) from distinct embryonic origins differ in their ability to support endothelial network formation. Lateral mesoderm-derived SMCs best support endothelial cell network complexity and survival in vitro, in part through increased expression of midkine. A lineage-specific approach might be beneficial for vascular tissue engineering and therapeutic revascularization.